Survey on Ethnobotanic Value of Banana (Musa spp; Musaceae) in Bali Province, Indonesia - Topik Hidayat; Himalaya Wana Kelana; Dhiyassalam Imam Anshori Ismanto; Karlia Meitha (Bogor Agricultural University, Indonesia, 2018)
Bali, one of Indonesia island, is a region inhabited by a large number and varied banana (Musa spp; Musaceae). Many varieties of banana have been utilized by local peoples since long time ago as traditional medicine, edible material, used in traditional ceremony and others. However, information regarding the knowledge on ethnobotany of banana in Bali remains scattered and is not documented well. The purpose of this study was to evaluate and document the ethnobotanic values of bananas in Bali. Ethnobotanic data was collected through focus group discussion (FGD), surveys and interviews from 9 study sites (1 city and 8 regencies) with one or two villages represented each site. Ethnobotanical value of banana was determined by Local User’s Value Index (LUVI) with Pebble Distribution Method (PDM). Subsequently, data obtained was analysed using simple statistic description. Results showed that as many as 44 varieties of banana in Bali were documented. Local peoples have been utilizing banana in their daily life for ritual as indicated by higher LUVI (0.4867), followed by food (0.3), medicine (0.1533), and other (0.06). On the basis of testimony of respondents, indigenous knowledge of peoples in Bali about banana is vertically transmitted from parents to their children (98%). This study provided a valuable information of how the local peoples manage and conserve the banana and its nature.